Property Subject to Investment - Aneta ZAREMBA (Communications of International Proceedings, 2022)
The concept of investing is probably familiar to anyone who comes into contact with money. Of course, investing involves spending money in order to benefit yourself at a later date. An investor has many choices of deposits, from the traditional bank deposit to real estate assets. There is a growing interest in real estate deposits among investors and non-investors alike. The main factor leading to economic development, is undoubtedly investing in real estate, which among many goods traded economically and legally, have the greatest importance for the development of the national economy. Investing in real estate is one of the ways of investing, along with such investment opportunities as, among others, purchasing shares in business entities and investment funds, as well as securities. In recent years, investing in real estate has found more and more supporters, the ever-increasing inflation prompts a large part of the population to find an appropriate and safe haven for their capital surpluses, and this has a very strong impact on demand. In addition, the still very low interest rates mean that keeping money in the bank is no longer in any way attractive, from an investment point of view.
Keywords: property; investment; investing